Sistem Informasi Pelayanan Klinik Terintegrasi WhatsApp Gateway dengan Evaluasi Kualitas Layanan Menggunakan SERVQUAL - M. Prahmana Tirta; Fathiya Hasyifah Sibarani (Sekawan Institut, 2026)
Clinic services at Bidan Arisanti Clinic still face challenges, including manual patient registration and data recording, inefficient information delivery, unintegrated queue management, and the absence of structured service quality evaluation. This study develops a web-based Clinic Service Information System integrating a WhatsApp Gateway and SERVQUAL. The system was developed using the Waterfall model, with data collected through observation, interviews, documentation, and a SERVQUAL questionnaire involving 30 patients. Black Box Testing was used to evaluate system functionality, while service quality was assessed based on the gap between patient expectations and perceptions. The results show that all system functions operated according to the specified functional requirements. SERVQUAL results produced an average expectation score of 4.69, perception score of 4.49, and gap value of -0.20, indicating that service quality has not fully met patient expectations. Responsiveness had the largest gap (-0.33), making it the main priority for improvement, particularly in service speed and staff responsiveness. The study provides an integrated system for service management, automated WhatsApp notifications, and SERVQUAL-based quality evaluation to support continuous service quality improvement.